Clay Minerals From The Upper Aptian Codó Formation, Grajaú Basin, Northeastern Brazil (Latin American Journal of Sedimentology and Basin Analysis, 2021)
This work combines facies, stratigraphy, X-ray diffraction, SEM and petrographic analyses in order to investigate argillaceous rocks of the Codó Formation exposed in the Codó and Grajaú areas, northeastern Brazil (Fig. 1). The main goal is to characterize the clay mineral assemblage and record its variability along the depositional cycles in the attempt to discuss its origin and test its applicability as paleoclimatic and paleoenvironmental proxy indicators.The Codó Formation records the Upper Aptian deposition of the Grajaú Basin, a tectonically subsiding structure originated during the early stages of rifting that culminated with the opening of the South Atlantic Ocean along the Equatorial Brazilian Margin (Aranha et al., 1990). This basin has been interpreted as a unique structure consisting of an intracontinental semi-graben, which was formed by combination of pure shear stress and strike-slip deformation (Góes and Rossetti, 2001). The sedimentary successions of this basin include three depositional sequences, designated as S1, S2 and S3 (Rossetti, 2001; Fig. 2), with the first including the Codó Formation studied herein.The Codó Formation records a depositional system dominated by closed and hypersaline lakes and sabkhasalt pan complex (Paz, 2000; Paz & Rossetti, 2001; Paz & Rossetti, 2005a). In the Codó area, these deposits encompass a 25 m-thick prograding lacustrine succession arranged as shallowing-upward cycles that are attributed to central, transitional, and marginal lake facies associations. Central lake deposits include mostly evaporites and bituminous black shales. Transitional lake deposits consist of green to grey shales interbedded with limestones (lime-mudstone, laminated to massive peloidal wackestone to packstone and sparstone) formed in more oxygenated waters relative to the central lake deposits. Marginal lake deposits include massive and indurated pelite with brownish-red colours, fenestral calcarenite of calcite grains, ostracodal wackestone/ grainstone, pisoidal packstone, rhythmite of ostracodal wackestone/grainstone, shale and microbial mats. These deposits show an abundance of features (i.e., paleosols, karstic features, fenestrae, meteoric cements, vadose pisoids) that are typically developed under exposure to subaerial conditions and/or meteoric waters. In the Grajaú area, evaporites dominate over the other facies, being represented by laminated gypsum and gypsare-nite/gypsrudite.The muddy lithofacies used in this study included black shale with high organic matter content, green to grey shale with low organic matter content, lime-mud-stone, rhythmite of carbonate and shale, and massive pelite. The black shales and the green to grey shales show a clay mineral assemblage composed of smectite (Fig. 3a and b) and, subordinately, illite (Fig. 3b), kaolinite (Fig. 3c) and irregularly interstratified illitesmectite. The smectite is, in general, detrital in nature, being characterized by crenulated flakes with parallel or chaotic arrangements (Figs. 3a and b). The smectite, when pure, exhibits high crystallinity and has been classified as dioctaedral montmorillonite. Authigenic smectite is locally found and arranged as crystals averaging 2 ?m that show a honey-comb morphology, which usually drape ostracode shells in rhythmites. Kaolinite occurs as pseudohexagonal and equidimensional crystals averaging 1 ?m in diameter that replaces smectite, and as booklets averaging 8 ?m that fill pores (Fig. 3c). Its occurrence is substantially increased in marginal lake deposits, more specifically in the massive pelite facies. Illite occurs as hair-like crystals (Fig. 3b, arrows) in transitional lake deposits as replacement of smectite. However, it is possible that part of this mineral is detrital; in this case, it is characterized by a morphology in flakes that can hardly be differentiated from detrital smectites.The lime-mudstone consists of calcite, sulphates, quartz grains and clay minerals similar to the ones found in the other sedimentary facies analysed in this study (Fig. 3d). The rhythmite of black shale/mudstone, typical of the marginal lake facies association, consists of parallel and laterally continuous laminae of microbial mats and/or green-grey shale that alternate with mudstone to ostracodal packstone/grainstone that locally display ostracod shells arranged parallel to bedding (Fig. 3e and f). The dominant clay mineral in this facies is also smectite, which occurs either as parallel flakes with ragged margins or as honeycomb crystals (Fig. 3g). The massive pelite (Fig. 3h, i), typical of marginal lake deposits, is composed by calcite, clay minerals and quartz grains (Fig. 3h). The clay minerals include smectite flakes with ragged margins, as well as hairy illite and booklets of kaolinites that are up to 12 ?m of length (Fig. 3i).Analysis of the X-ray diffractograms revealed that mixed illite/smectite interlayers are also present in the deposits characterized above (Fig. 4). The distribution of smectite and illite/smectite throughout the studied profiles shows an upward decrease relative to the amount of kaolinite and illite (Figs. 5 and 6). This tendency was also observed in some individual shallowing-upward cycles. Thus, central and transitional lacustrine deposits, located at the base of the successions, exhibit relatively increased amounts of smectite relative to kaolinite and illite, while the transitional and marginal deposits at the top show an inverse behavior. The large volume of detrital clay minerals allowed their use for discussing depositional paleoenvironment and paleoclimate. The dominance of detrital smectites revealed deposition from suspensions throughout the depositional setting, supporting low energy flows, typical of lacustrine and sabkha-salt pan complex, as proposed for the study area with basis on facies analysis. The presence of clays as the only clastics reveals a basin located in a region with low topography, and the species montmorillonite (Tabelas 1, 2 and 3) attests to continental areas. Despite the authigenic origin, the occurrence of the highest volumes of kaolinite and illite systematically at the top of the shallowing-upward cycles suggests influence of the depositional setting. Hence, a model is proposed where detrital smectites were introduced in large volumes into depressed areas during periods of high base level. As the inflow, and consequently, the base level dropped, the water level decreased, promoting alternation of clastic and chemical deposition under fluctuating subaqueous and subaerial conditions.A semi quantitative study applying EDS revealed that smectites from the black shales contain higher Al relative to Mg, as well as significant values of K (Fig. 7). In addition, the green-grey shales and massive pelite display smectites with Si occupying a tetrahedric position (Tabelas 2 and 3). The octahedric position is occupied by Al, Mg, Fe3+ and, secondarily, Ti. The excess of K confirms the presence of an illitic composition, associated with interestratified illite/smectite.The formation of kaolinite and illite from detrital smectites would have occurred under influence of subaerial exposure and pedogenesis. Further studies are still needed in order to better understand the origin of these authigenic minerals. However, the occurrence of both minerals in a same stratigraphic horizon, associated with marginal lacustrine facies from the top of shallowing upward cycles led to invoke a possible climatic influence. Hence, the formation of illite would have occurred under increased evaporation (drier periods), while the kaolinite would have formed due to the influence of phreatic waters having low pH (relatively more humid periods). The dominance of detrital montmorillonite suggests its formation as a consequence of weathering in continental arid areas. These characteristics, added to the vast presence of evaporites in the study areas, led to indicate a prevailing hot, arid to semi-arid climate during the Late Aptian of the Grajaú Basin.
Keywords: Paleoclimate; Paleoenvironment; Clay minerals; Late Aptian; Northeastern Brazil